2014
DOI: 10.1177/0731948714524752
|View full text |Cite
|
Sign up to set email alerts
|

Can Curriculum-Embedded Measures Predict the Later Reading Achievement of Kindergarteners at Risk of Reading Disability?

Abstract: This study examined the changing role and longitudinal predictive validity of curriculum-embedded progress-monitoring measures (CEMs ) for kindergarten students receiving Tier 2 intervention and identified as at risk of developing reading difficulties. Multiple measures were examined to determine whether they could predict comprehensive latent first-and second-grade reading outcomes and whether their predictive validity changed concurrent with reading development. CEMs of phonemic, alphabetic, and integrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Curriculum embedded word decoding We monitored the progress of word decoding with curriculum embedded word decoding tasks. Curriculum Embedded Measurements (CEMs) assess the mastery levels of skills that have been taught explicitly, evolving in alignment with instruction (Oslund et al, 2015 ). Curriculum embedded assessments are suitable methods for obtaining meaningful information from the very first steps in reading development while standardized measurements would be too rough and general to identify individual differences (floor level results).…”
Section: Methodsmentioning
confidence: 99%
“…Curriculum embedded word decoding We monitored the progress of word decoding with curriculum embedded word decoding tasks. Curriculum Embedded Measurements (CEMs) assess the mastery levels of skills that have been taught explicitly, evolving in alignment with instruction (Oslund et al, 2015 ). Curriculum embedded assessments are suitable methods for obtaining meaningful information from the very first steps in reading development while standardized measurements would be too rough and general to identify individual differences (floor level results).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies [42,45,73] have similarly concluded that there is minimal value in assessing cognitive characteristics for the purpose of predicting how children will respond to intervention. Put simply, the additional information such assessments can provide, above and beyond that yielded by baseline academic assessment or curriculum based or embedded measures [74] appears not to be worth the investment of resources that is required. Stuebing et al (2015) [73] undertook a meta-analysis of 28 studies of young children (third grade and younger) in order to answer the question: What is the magnitude between various baseline child cognitive characteristics and responses to reading intervention?…”
Section: Predicting Academic Progressmentioning
confidence: 99%
“…After each curriculum‐based training block of 3–4 weeks, word decoding mastery level up until then was measured by embedded assessment cards Veilig en Vlot (‘Safe and Smooth’; Mommers et al, ). Because the assessment cards were specifically designed to measure the short‐term attainment of recently taught skills, the consecutive measurements were not equivalent but instead developed along with the content of the curriculum (see also Oslund et al, ) for further explanation of curriculum‐embedded measurement. The words on the assessment cards were composed of the graphemes and structures that the children had trained on during the previous blocks.…”
Section: Methodsmentioning
confidence: 99%
“…Snowling, Muter, & Carroll, 2007;Van Bergen et al, 2011). However, the large intervals being used in these few studies do not capture the children's earliest developmental trajectory as also explained by Fuchs, Fuchs, and Compton (2004) and by Oslund et al (2015). The actual emergence of the reading problems of children at risk has thus not been extensively documented before, and the relation between the precursor measures and the early word decoding development in children at risk still remains unclear.…”
mentioning
confidence: 99%